Gest??o da mem??ria organizacional com transfer??ncia do conhecimento e melhoria de um processo cr??tico: o caso de uma ag??ncia reguladora brasileira - Corr??a, Rony Figueredo (2017)
Research conducted by IPEA, in 2014, showed that 70% of Brazilian public institutions are in the early stages of implementing knowledge management - KM - and in this stage the KM is not able to produce benefits for the organization. Besides this low maturity index, there is little research on success cases in the implementation of KM in the Brazilian public administration. Faced with this scenario, this case study aims to investigate how the National Civil Aviation Agency (ANAC), an Brazilian federal public administration body, was successful in implementing knowledge transfer practices to improve the airworthiness certificate issuance process, reducing waiting time of issuing the certificate from 12 to 2.4 days. Thus, from a theoretical point of view, this study intends to compare the findings with the results of empirical studies found in the KM literature that indicates a positive relationship between KM, innovation and organizational performance. As a practical contribution, analyze how the implementation of knowledge transfer practices allowed a public organization to improve the performance of a critical process.